Determining Inland Waterway Parameters with Application to the Sava River - Pršić, Marko; Carević, Dalibor; Brčić, Davor (Promet - Traffic&Transportation, 2012)
The article provides a definition of inland waterway parameters with the emphasis on the international waterway classes IV, Va and Vb relevant to the Sava River. The parameters have been defined through the comparative analysis based on international classification of inland waterways, the available theoretical assumptions, and available and published physical model researches. The channel parameter problems have not been considered herein. The philosophy of the applicable UN/ECE classification of 1992 consists in defining the relevant waterway structures and navigable water levels only. The waterway parameters are then determined in compliance therewith for each individual waterway based on the navigable channel morphology, through the morphological, technical and economic analysis. Through such an iterative procedure, a detailed standardization of the Sava River waterway parameters was created for the international classes IV, Va and Vb, serving as basis for the current analysis of the Sava River navigability for the purpose of gaining informative concept of the scope of water works to be executed and the financial dimension of requested works for short-term and long-term periods. KEY WORDS: inland waterway, the Sava River, waterway class, standardization, river bed morphology